Race and Public Administration - Rutherford, Amanda; Meier, Kenneth J. (Taylor & Francis, 2020)
Issues of race permeate virtually every corner of policy creation and implementation in the United States, yet theoretically driven research on interactions of policy, race, and ethnicity rarely offers practical tools that can be readily applied by current and future civil servants, private contractors, or nonprofit boards. Arguing that scholarship can and should inform practice to address issues of equity in public affairs, rather than overlook, ignore, or deny them, Race and Public Administration offers a much-needed and accessible exploration of current and cutting-edge research on race and policy. This book evaluates what contradictions, unanswered questions, and best (or worst) practices exist in conducting and understanding research that can provide evidence-based policy and management guidance to practitioners in the field.　 Individual chapters are written by established and emerging scholars and explore a wide range of policy areas, including public education, policing, health and access to healthcare, digital governance, nonprofit diversity, and international contexts. Together, the chapters serve as a link between theoretically informed research in public administration and those students and professionals trained to work in the trenches of public administration. This book is ideally suited as a text for courses in schools of public administration, public policy, or nonprofit management, and is required reading for those actively involved in policy analysis, creation, or evaluation.